PENINGKATAN PENGETAHUAN MASAYARAKAT DALAM MENGOLAH SAMPAH ORGANIK DI PKK DESA BADEAN BLIMBINGSARI BANYUWANGI - Mushoffa, Mushoffa; , Muhammad Zulqurnain; Ana Nurjanah (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
Waste management has become a significant challenge in many regions, including Badean Village, Blimbingsari, Banyuwangi, where the volume of organic waste has increased due to population growth and economic activities. This community service program aimed to empower the local PKK (Family Welfare Program) women by training them in organic waste management through composting, Local Microorganisms (MOL) production, and eco-enzyme techniques. The program was conducted in two phases, on August 27-28 and October 1-2, 2024, involving experts, students, and village officials. The results showed an improvement in participants' knowledge and skills in transforming organic waste into valuable products such as organic fertilizers and multifunctional liquids. The effectiveness of the training was demonstrated by increased community participation in sustainable waste management. This program is expected to contribute to reducing waste volume in the village and enhance community welfare through the utilization of organic waste.